The Role of Forensic Accounting in Detecting Financial Fraud in Emerging Markets - Asbe, Dr. Chetana; Sahoo , Dr. Anita; Khan , Dr.P. Hameem; Kalidhas , AravindanMunusamy; Kapila , Ish; Aggarwal , Prateek; Agrawal , Dr. Neha (International Journal of Accounting and Economics Studies, 2025)
We address the role of forensic accounting through a thorough analysis of financial documents, the identification of anomalous patterns of activity, collaboration with law enforcement and security agencies, and the prevention of fraud through the installation of financial controls, all of which are accomplished through a systematic literature review approach.The results demonstrate that forensic accounting is not just a preventive measure to lessen the probability of future financial fraud but also a poor post-event strategy.This is an attempt to provide a broad overview of the critical role that forensic accounting plays in preserving a company's financial integrity by summarizing these findings.The purpose of this study is to examine the important role that forensic accounting plays in identifying and looking into financial wrongdoing. The method of research employed is literature. Forensic accountants utilize evidence-gathering tools and techniques of special investigation to identify anomalous patterns that can indicate fraud. Their experience and training in evidence examination and preparation of investigative reports are of vital support during legal proceedings. The results also affirm that forensic accountants have a crucial role as expert witnesses in the courtroom, and in making recommendations for the improvement of internal control systems to mitigate the risk of future fraud.